PEMBERDAYAAN MASYARAKAT KEPULAUAN TALANGO KABUPATEN SUMENEP MELALUI USAHA PERCETAKAN DAN SABLON DIGITAL PRINTING - Budi Dwi Satoto; Bain Khusnul Khotimah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2014)
The role of youth in development is very important because it is considered to be in the productive age to support various development activities in various sectors. Most youth can be absorbed in the labor market, and partly eliminated from the competition and become a static group. Not a few who engage in the business world ranging from the small to large, one form of business that is highly demanded by the youth is the Small and Medium Enterprises and Silk Screen Printing. However, the form of efforts among youth most still use manual design and printing due to lack of capital and expertise. With this activity, try to solve them with IBM is working with partners Silk Screen Printing Industry centers in villages Talango, Talango islands, Sumenep, Disperindag and local cooperative activities such as application of digital printing techniques, the design theme oflocal wisdom Madura images with coloror multi color mono color and entrepreneurship training and business management. IBM activity was done in the form of training, coaching and mentoring the youth group field of screen printing and printing for souvenirs and handicrafts which aims to: 1) increase the motivation of entrepreneurial partners; 2) improve the understanding of partner business planning and business management; 3) improve human resource capabilities in the production and marketing techniques; 4) develop a network to support youth entrepreneurship development of the creative economy. Youth empowerment group is expected to produce a model that can be used as a model youth entrepreneurial development youth empowerment-based society.Keywords: training, coaching, mentoring, printingandscreen printing, digital printing